Survey on mortality rate of young stock on dairy farms of the Province of Padova - Lora, Isabella; Paparella, Paolo; Brscic, Marta; Gottardo, Flaviana (Acta Agraria Kaposváriensis, 2014)
The present study aimed at investigating preliminarily the mortality rate in 2012 of replacement calves and heifers in 95 dairy farms in the Province of Padova. Data regarding total number of cows and replacement stock reared were gathered from the APA Breeders’ Association records while data on number of dead replacement animals were collected from insurance records. Results showed that the median value of the overall mortality rate of replacement cattle
Keywords: calf; replacement dairy cattle; mortality